(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The aim of this study is to assess the adaptability and productivity of winter wheat varieties under variable weather conditions by analysing grain yield, 1000-grain weight (TGW), and protein content through long-term trials, as well as evaluating the impact of nitrogen fertilisation in short-term case studies. A field trials study assesses the performance of long-established (over 13 growing seasons) and newly introduced wheat varieties (one growing season at two locations). Seven significant correlations between weather conditions and grain yield, TGW, and protein content were recorded for the varieties 'Skagen' and 'Brons' over a long-term period. ‘Skagen’ and ‘Brons’ are well-adapted to the local conditions in Latvia. Negative correlations were observed between grain yield and mean temperatures in July at Vilani (r = −0.60; r = −0.73 for both varieties), as well as between total precipitation in September (rSkagen = −0.73) at Stende. Additionally, negative correlations were found between TGW and mean temperatures in June (rSkagen = −0.72; rSkagen = −0.64) at both locations, while a positive correlation was observed between total precipitation in June (rSkagen = 0.73) at Stende. Positive correlations were also recorded between protein content and total precipitation in May and June at Vilani (r = 0.59; r = 0.71) for both varieties. Negative correlation was identified between protein contents and total precipitation in April (r = −0.68; r = −0.69) for both varieties and positive correlation mean temperatures in June (rSkagen = 0.57) at Stende. One growing season compared the effects of nitrogen fertilisation N0, N120, N180 treatments on wheat varieties 'Bright', 'Brigens', 'KWS Ahoi', and 'KWS Imperium' at two locations. At N180, the mean values for the four varieties were significant higher at Vilani and Stende compared to the control. The highest grain yield was recorded for the variety 'Bright' at Stende and for 'KWS Ahoi' at Vilani. The variety ‘Brigens’ was identified as having the high protein content and TGW at both locations. These findings provide insights into sustainable wheat cultivation, with a short-term study ongoing to further develop resilient growing systems.